Teori perkembangan Lev Vey Gotskyeleme - Mahmuda, Faridhatul (Maliki Interdisciplinary Journal, 2024)
To understand children's cognitive development, understanding character formation to improve memory and reasoning is necessary. Children's cognitive development is very important to pay attention to because it requires the child's understanding of character formation, which means more reasoning about character formation to increase the possibility of strong memory and reasoning. Thus, early childhood develops their learning first and children must carry out this development not from the social environment, therefore children prefer to learn alone rather than in other people's environments, therefore children do not develop in very active activities, regarding character formation to improve the possibility of memory and reasoning is that children can do whatever they want, therefore children cannot develop in what they do with the development of the language they use, therefore children must be taught correctly so that children can develop quickly, Piaget said that children can explore the world quickly therefore society must encourage children to be more persistent because children have an environment that is very uneducative therefore children must do it quickly, children must be able to manage skills outside and children must learn quickly because they have to do activities outside .